2009
DOI: 10.1021/ja907125t
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated IgE−Receptor Aggregation and Signaling in RBL Mast Cells

Abstract: Complex cell behaviors are usually triggered by multivalent ligands that first bind to membrane receptors and then promote receptor clustering, thus altering intracellular signal transduction. While it is possible to produce such altered signal transduction by synthetic means, the development of chemically defined multivalent ligands of effectors is sometimes difficult and tedious. Specifically, the average spacing between two binding sites within an antibody and the average distance between receptors on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 31 publications
8
87
0
Order By: Relevance
“…Such effects previously were reported based on experiments and theory (35,36). Multivalent gold nanoparticles coated with dinitrophenyl have shown a similar bell-shaped dose-response curve due to cross-linking of IgEFceRI receptor complexes in RBL-2H3 mast cells (37). Although the studies presented here suggest that enhanced uptake of nanorods can be explained by enhanced surface binding, additional factors associated with multivalent interactions and penetration through the glycocalyx also are likely explanations for the experimental observations (SI Text, section 5).…”
Section: Discussionsupporting
confidence: 61%
“…Such effects previously were reported based on experiments and theory (35,36). Multivalent gold nanoparticles coated with dinitrophenyl have shown a similar bell-shaped dose-response curve due to cross-linking of IgEFceRI receptor complexes in RBL-2H3 mast cells (37). Although the studies presented here suggest that enhanced uptake of nanorods can be explained by enhanced surface binding, additional factors associated with multivalent interactions and penetration through the glycocalyx also are likely explanations for the experimental observations (SI Text, section 5).…”
Section: Discussionsupporting
confidence: 61%
“…These findings confirm the results of Huang et. al.,20 in demonstrating that NPs can interact directly with FcεRI and also extend these results by reporting that even smaller particles (3–10 nm) can inhibit cell effector functions.…”
Section: Discussionsupporting
confidence: 58%
“…Huang et al20 showed that DNP‐albumin labeled gold NPs directly stimulated FcεRI‐mediated responses by providing cross‐linking of receptors. However, bare gold particles themselves did not bind to FcεRI, nor did they alter degranulatory behavior.…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs has been used as substrate to immobilize electrochemical marker to amplify the electrochemical signal in recent years. It's obviously that there needs no enzymes in this procedure [24].…”
Section: Introductionmentioning
confidence: 99%